1999
DOI: 10.1002/1529-0131(199901)42:1<39::aid-anr5>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum cartilage marker levels indicate altered cartilage metabolism in families with the osteoarthritis-related type II collagen gene COL2A1 mutation

Abstract: Study of the macromolecular constituents of cartilage released into serum in subjects with familial OA revealed altered metabolism in OA, as demonstrated by elevated COMP and KS levels. Other constituents, the 846 epitope and CPII, were not altered, indicating dissociation of cartilage anabolism and breakdown. Future sequential studies will provide an opportunity to define biochemical changes as familial OA develops and to monitor therapeutic responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…This may be explained by the fact that long duration of the disease is likely to result in more cartilage destruction with consequent release of aggrecan into the joint fluid which then appears in the serum. These findings are in agreement with that reported in some literatures [30,36,37]. However, Sharif et al [38] and Conrozier et al [35] disagreed with our findings and postulated that increased expression of these epitopes might reflect the response of the articular cartilage to insult requiring initiation of a high level.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This may be explained by the fact that long duration of the disease is likely to result in more cartilage destruction with consequent release of aggrecan into the joint fluid which then appears in the serum. These findings are in agreement with that reported in some literatures [30,36,37]. However, Sharif et al [38] and Conrozier et al [35] disagreed with our findings and postulated that increased expression of these epitopes might reflect the response of the articular cartilage to insult requiring initiation of a high level.…”
Section: Discussionsupporting
confidence: 92%
“…These findings could be explained by the fact that clinical evaluation does not necessarily reflect cartilage changes as no close link between such parameters and the tissue process was to be expected [32,35,39,40]. These results disagree with those of Campion et al [41], Thonar et al [42] and Bleasel et al [30] who reported that aggrecan turnover correlated positively with the clinical signs of knee OA. Moreover, Sharif et al [38] found that COMP levels significantly correlated with activity and severity of knee OA.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Over the last decade, investigators have explored several candidate markers that quantify macromolecules (or their fragments) that are specific to, or most prominent in, cartilage, including the proteoglycan aggrecan (1-3), type II collagen (4)(5)(6)(7)(8), and cartilage oligomeric matrix protein (9,10). The ability to measure such metabolites in joint fluid, serum, and urine holds promise for clinically useful ways of diagnosing, staging, and monitoring the progression and therapeutic response of joint tissues to injury and disease.…”
mentioning
confidence: 99%
“…4,5 Functionally, COMP facilitates type II collagen fibril assembly, enhances chondrocyte attachment in vitro, and interacts with other ECM proteins, including type II and IX collagens, matrilin 3, and SPARC. [6][7][8][9][10][11][12] In contrast, mutations in COMP cause misfolding of the protein, preventing export from the chondrocyte and resulting in massive retention within the endoplasmic reticulum (ER). 10,[13][14][15] Although this finding has long been appreciated, there was little understanding of the pathologic molecular mechanisms, which are critical to develop mechanism-driven therapeutics.…”
Section: Introductionmentioning
confidence: 99%